2018
DOI: 10.1177/2158244018788616
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Intercultural Competence in Bilingual Programs in Indonesia

Abstract: Most studies of intercultural competence in bilingual programs have been conducted in non-Asian contexts resulting in little information on how Indonesian educators promote intercultural values within bilingual programs. This research contributes to the body of literature that examines the promotion of intercultural values within bilingual higher education in Indonesia. It focuses on lecturers' perceptions of their strategies to teach and promote intercultural values in Indonesian higher education institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…This paper is in line with other studies that analyze the intercultural awareness of bilinguals (e.g. Arasaratnam-Smith, 2016;Abduh and Rosmaladewi, 2018;Gómez-Parra, 2020), their employability (e.g. Callahan and Gándara, 2014;Yang, 2015;Jongyeon, 2019), and their mobility (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…This paper is in line with other studies that analyze the intercultural awareness of bilinguals (e.g. Arasaratnam-Smith, 2016;Abduh and Rosmaladewi, 2018;Gómez-Parra, 2020), their employability (e.g. Callahan and Gándara, 2014;Yang, 2015;Jongyeon, 2019), and their mobility (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, a plethora of studies which discuss IC have been investigated by several researchers in the Indonesian context (Abduh & Rosmaladewi, 2018;Adi, 2017;Aprianoto & Haerazi, 2019;Dollah, Syarifuddin, Abduh, Amirullah, Talib, 2017;Edi, Wello, & Dollah, 2017;Haerazi, Irwansyah, Dedi & Azis, 2018;Idris, 2020;Idris & Widyantoro, 2019;Luthfia, Rosidah, & Sofian, 2019;Miftakh, 2017;Mumu, 2017;Rosyidi & Purwati, 2018;Sabilah, 2018;Siregar, 2016;Yulianti, 2019;Zacharias, 2005); however, limited studies discussing this amid COVID-19 pandemic was found. Thus, to fill the gap of the previous related studies, it is deemed necessary to carry out a study concerning this area, i.e., challenges and opportunities encountered in intercultural language teaching, particularly during the COVID-19 pandemic based on the teachers' perspectives since they are the primary executor of the instruction conducted.…”
Section: Introductionmentioning
confidence: 99%
“…For Indonesian higher education, the use of web-based instruction is a new change that happened in the last few years, mainly for soft and hard science. Some researchers investigated the influence of online technologies in language learning: learners aspiration in utilizing technology for learning [25], the use of Instagram for language learning [26], mobile-assisted language learning [27], learners can use technology for their vocabulary development [28], online learning and gamification [29], the culture of language learning [30]- [32], podcast and language learning [33], internationalization awareness and commitment for learning [34], technology and historical literacy [35], literacy and anthropology in higher education [36], literacy in vocational education [37], intercultural literacy [38], technology, oral and written literacy [39], [40], and hybrid-eLearning [41]. Among the studies, none of them have focused on holistic skill development because of online learning and explore the challenges of online education.…”
Section: Introductionmentioning
confidence: 99%